TRANSLATION TECHNIQUE ANALYSIS OF CARL’S UTTERANCES AS THE MAIN CHARACTER IN THE UP MOVIE SUBTITLES - Agustiani, Agustiani; Jumanto, Jumanto (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2023)
This paper is entitled Translation Technique Analysis of Carl’s Utterances as The Main Character in UP Movie Subtitles. This research focuses on the analysis of translation techniques based on the UP Movie subtitles. The source of data in this research is Carl’s utterances as the main character in this movie. The objectives of this research are to find out the translation techniques applied by the translator in the UP Movie subtitles. This research uses a qualitative method to explore the objectives of the research. The results are found by the researcher from 170 utterances that were divided into several words, phrases, clauses and also sentences. The research findings show that the translator applies 13 types of translation techniques. Based on the biggest frequencies of occurences, they are as follows: (1) Literal Translation, (2) Establish Equivalence, (3) Amplification, (4) Reduction, (5) Borrowing, (6) Transposition, (7) Linguistic Amplification, (8) Linguistic Compression, (9) Adaption, (10) Modulation, (11) Calque, (12) Particulation, (13) Description. Based on the analysis that has been done, there are few types of translation techniques used in this movie. The researcher needs to pay attention to the rules of each translation technique to find the correct analysis, and to find out and describe the dominant translation technique in this research, that is the literal translation technique. The translator mostly uses literal translation technique to translate the movie subtitles because the genre of this movie is mainly aimed to entertain children. Children are the target audience of this movie.